1999
DOI: 10.1111/j.1751-1097.1999.tb08261.x
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Targeting of Ovarian Cancer with the Photosensitizer PEG‐m‐THPC in a Rat Model

Abstract: Photodynamic therapy (PDT) uses light to activate a photosensitizer that has been absorbed or retained preferentially by cancer cells after systemic administration. The first pegylated photosensitizer, tetrakis-(m-methoxypolyethylene glycol) derivative of 7,8-dihydro-5,10,15,20-tetrakis(3-hydroxyphenyl)-21,23-[H]-porphyrin (PEG-m-THPC), was evaluated to target selectively unresectable pelvic ovarian cancer bulks. Our goals were two-fold: (1) to establish an ovarian cancer model suitable for the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Chinese hamster lung fibroblasts (223), human colorectal carcinoma cells (470) and xenografts (467) and murine leukemic cells L1210 (470). Other examples were studies on ovarian cancer cells (474) with very high tumor/tissue ratios (280) and liver tumor models (478), which showed no significant advantage. For example, m THPC‐MD 2000 in a rat colon adenocarcinoma resulted in an increase of PS concentration in the liver with time, thus resulting in a loss of tumor selectivity (478).…”
Section: Related Sensitizers and Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chinese hamster lung fibroblasts (223), human colorectal carcinoma cells (470) and xenografts (467) and murine leukemic cells L1210 (470). Other examples were studies on ovarian cancer cells (474) with very high tumor/tissue ratios (280) and liver tumor models (478), which showed no significant advantage. For example, m THPC‐MD 2000 in a rat colon adenocarcinoma resulted in an increase of PS concentration in the liver with time, thus resulting in a loss of tumor selectivity (478).…”
Section: Related Sensitizers and Developmentsmentioning
confidence: 99%
“…A NuTu‐19 ovarian cancer rat model was developed and used for testing debulking techniques. Use of m THPC‐PEG gave a very high (40 ± 12) tumor/tissue ratio after 8 days (280).…”
mentioning
confidence: 99%
“…These systems tend to increase plasma lifetimes and tumor uptake, by decreasing the drug accumulation in liver and other organs of the reticuloendothelial system [138][139][140]. A hydrophilic derivative of m-THPC bearing four polyethylene glycol side chains (6-PEG) was found to be highly selective for NuTu-19 ovarian tumors in rats [141], although no specificity was found in a rat liver tumor model, as a consequence of concomitant uptake by normal liver tissue [142]. Water-soluble Al(III)-phthalocyanine derivatives bearing a polyethylene glycol or a polyvinylalcohol chain coordinated to the aluminum ion were shown to be as efficient as Al(III)-phthalocyanine in CRM emulsion for the PDT treatment of EMT-6 tumors in mice [143].…”
Section: Delivery Vehicle-mediated Tumor Targetingmentioning
confidence: 99%
“…( 7,8 ) Hornung et al . ( 9,10 ) showed that intraperitoneal PDT, as a minimally invasive procedure, could selectively debulk unresectable pelvic ovarian cancer in immunocompetent rats using the pegylated photosensitizer PEG‐m‐THPC, which was confirmed to be highly targeted to ovarian cancer in a rat model. Several clinical trials using first‐generation photosensitizer dihematoporphyrin ether and porfimer sodium showed the therapeutic effects of PDT in treating peritoneal malignancy including ovarian cancer.…”
mentioning
confidence: 99%